PROGRESSIVE WEB APPS: evaluate an application in different browsers and operating systems - Tiosso, Fernando; Izaki, Brian Kazuyoshi; Reis, Helena Macedo (Revista Interface Tecnológica, 2021)
This work aims to evaluate the compatibility of a Progressive Web Application (PWA) in relation to its support for a native application experience on Android and iOS Operating Systems (OSes) using Chrome, Firefox, Samsung Internet and Safari browsers. Through bibliographic searches in books, documentation and manufacturers websites, it was observed which are the most relevant characteristics that could be used during the analysis of the application for mobile devices until the present moment, providing the development and analysis of a properly audited PWA and recognized by the Lighthouse app. Thus, through the evaluations carried out, it was found that the Android operating system and the Chrome browser offered greater support for a native application experience using the progressive approach.